2014
DOI: 10.1371/journal.pone.0091765
|View full text |Cite
|
Sign up to set email alerts
|

Structural Bases of Norovirus RNA Dependent RNA Polymerase Inhibition by Novel Suramin-Related Compounds

Abstract: Noroviruses (NV) are +ssRNA viruses responsible for severe gastroenteritis; no effective vaccines/antivirals are currently available. We previously identified Suramin (9) as a potent inhibitor of NV-RNA dependent RNA polymerase (NV-RdRp). Despite significant in vitro activities versus several pharmacological targets, Suramin clinical use is hampered by pharmacokinetics/toxicity problems. To improve Suramin access to NV-RdRp in vivo, a Suramin-derivative, 8, devoid of two sulphonate groups, was synthesized, ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 41 publications
1
50
0
Order By: Relevance
“…There has been significant progress in identifying small molecule inhibitors of NoV RdRp using in silico screening, and in understanding the structural basis of inhibition by analyzing co-crystal structures of RdRp with some of these inhibitors [85,86*]. Non-nucleoside inhibitors such as suramin, a drug used in the treatment of sleeping sickness caused by the protozoan Trypanosoma, and its analogue NF023, consisting of naphthalene-trisulfonic acid moiety, have been shown to be effective in inhibiting NoV RdRp with IC 50 s in low nanomolar range [86*].…”
Section: Non-structural Proteins As Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been significant progress in identifying small molecule inhibitors of NoV RdRp using in silico screening, and in understanding the structural basis of inhibition by analyzing co-crystal structures of RdRp with some of these inhibitors [85,86*]. Non-nucleoside inhibitors such as suramin, a drug used in the treatment of sleeping sickness caused by the protozoan Trypanosoma, and its analogue NF023, consisting of naphthalene-trisulfonic acid moiety, have been shown to be effective in inhibiting NoV RdRp with IC 50 s in low nanomolar range [86*].…”
Section: Non-structural Proteins As Targetsmentioning
confidence: 99%
“…Non-nucleoside inhibitors such as suramin, a drug used in the treatment of sleeping sickness caused by the protozoan Trypanosoma, and its analogue NF023, consisting of naphthalene-trisulfonic acid moiety, have been shown to be effective in inhibiting NoV RdRp with IC 50 s in low nanomolar range [86*]. Both these inhibitors bind RdRp along the nucleotide access pathway between the fingers and thumb domains (Fig.…”
Section: Non-structural Proteins As Targetsmentioning
confidence: 99%
“…NV RdRP itself is capable of both primed and de novo RNA synthesis . In vitro de novo‐initiated RNA synthesis‐based RdRP activity assays rely on the addition of Mn 2+ , or both Mn 2+ and Mg 2+ , and activity has been observed to be enhanced by increased concentrations of Mn 2+ , but not of Mg 2+ . Likewise, Mn 2+ has been shown to preferentially enable RNA synthesis by NV RdRP in vitro , and no strong preference for Mg 2+ versus Mn 2+ usage by NV polymerase has been reported …”
Section: Introductionmentioning
confidence: 99%
“…A more recent study reported that ribavirin resolved chronic HuNoV infection in two patients with common variable immunodeficiency, but did not have an effect in two other patients [106]. Other replication-dependent strategies have focused on compounds that inhibit the viral RdRp, such as suramin-related compounds [128]. Development of these compounds has previously been hampered by toxicity problems; modification of suramin reduced the toxicity but retained suramin’s ability to potently inhibit both human and murine NoV RdRps [128].…”
Section: Antinorovirus Drugsmentioning
confidence: 99%
“…Other replication-dependent strategies have focused on compounds that inhibit the viral RdRp, such as suramin-related compounds [128]. Development of these compounds has previously been hampered by toxicity problems; modification of suramin reduced the toxicity but retained suramin’s ability to potently inhibit both human and murine NoV RdRps [128]. The anti-NoV capabilities of these preexisting antiviral compounds increase the toolbox of healthcare professionals for treatment of persistently infected patients, while novel compounds are developed.…”
Section: Antinorovirus Drugsmentioning
confidence: 99%